Comparison of Logistics Performance Measurement Tools - Strommer, Diána; Földesi, Péter (Acta Technica Jaurinensis, 2019)
In today’s word the role of logistics is getting more important in the operation of enterprises. The competition is big, and cost is one of the most important factors. Logistics is a field which can highly support the reduction of the costs. From the other perspective – the customer satisfaction – logistics also has the role of a supportive function. To get the most out of these two big pillars logistics operation needs to be monitored and measured to give room for further improvement. Currently several methods are available for performance measurement. In this article we present comparison of four of the mainly used performance measurement tools.